Mab_3083c Is a Homologue of RNase J and Plays a Role in Colony Morphotype, Aggregation, and Sliding Motility of Mycobacterium abscessus - Liu, Ting-Yu (Microorganisms, 2021)
Mycobacterium abscessus is an opportunistic pathogen causing human diseases, especially in immunocompromised patients. M. abscessus strains with a rough morphotype are more virulent than those with a smooth morphotype. Morphotype switch may occur during a clinical infection. To investigate the genes involved in colony morphotype switching, we performed transposon mutagenesis in a rough clinical strain of M. abscessus. A morphotype switching mutant (smooth) named mab_3083c::Tn was obtained. This mutant was found to have a lower aggregative ability and a higher sliding motility than the wild type strain. However, its glycopeptidolipid (GPL) content remained the same as those of the wild type. Complementation of the mutant with a functional mab_3083c gene reverted its morphotype back to rough, indicating that mab_3083c is associated with colony morphology of M. abscessus. Bioinformatic analyses showed that mab_3083c has a 75.4% identity in amino acid sequence with the well-characterized ribonuclease J (RNase J) of M. smegmatis (RNase J(Msmeg)). Complementation of the mutant with the RNase J gene of M. smegmatis also switched its colony morphology from smooth back to rough. These results suggest that Mab_3083c is a homologue of RNase J and involved in regulating M. abscessus colony morphotype switching.